2012
DOI: 10.1002/art.34649
|View full text |Cite
|
Sign up to set email alerts
|

JAK inhibition with tofacitinib suppresses arthritic joint structural damage through decreased RANKL production

Abstract: Objective. The mechanistic link between Janus kinase (JAK) signaling and structural damage to arthritic joints in rheumatoid arthritis (RA) is poorly understood. This study was undertaken to investigate how selective inhibition of JAK with tofacitinib (CP-690,550) affects osteoclast-mediated bone resorption in a rat adjuvant-induced arthritis (AIA) model, as well as human T lymphocyte RANKL production and human osteoclast differentiation and function.Methods. Hind paw edema, inflammatory cell infiltration, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
80
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 45 publications
(61 reference statements)
4
80
0
Order By: Relevance
“…Single-dose tofacitinib data in mCIA demonstrated immediate effects of tofacitinib on plasma inflammatory mediators and in some cases sustained impact on chemotactic proteins, without an immediate bearing on the disease severity index. Rapid inhibition of IL-6, IP-10, and other inflammatory mediators has previously been demonstrated in mCIA and rat adjuvantinduced arthritis, and likely represents blockade of innate immune mechanisms (Ghoreschi et al, 2011;LaBranche et al, 2012). Sustained effects on innate immunity following tofacitinib administration would be consistent with a mechanism of prolonged modulation of transcriptional activity downstream of JAK signaling.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Single-dose tofacitinib data in mCIA demonstrated immediate effects of tofacitinib on plasma inflammatory mediators and in some cases sustained impact on chemotactic proteins, without an immediate bearing on the disease severity index. Rapid inhibition of IL-6, IP-10, and other inflammatory mediators has previously been demonstrated in mCIA and rat adjuvantinduced arthritis, and likely represents blockade of innate immune mechanisms (Ghoreschi et al, 2011;LaBranche et al, 2012). Sustained effects on innate immunity following tofacitinib administration would be consistent with a mechanism of prolonged modulation of transcriptional activity downstream of JAK signaling.…”
Section: Discussionmentioning
confidence: 61%
“…Studies in animal models of arthritis have indicated that JAK inhibition reduces signs and histologic manifestations of arthritis (Milici et al, 2006(Milici et al, , 2008Lin et al, 2010;Fridman et al, 2010). More specifically, tofacitinib treatment resulted in dose-dependent reduction in joint inflammation in mouse and rat arthritis models (Milici et al, 2008;Meyer et al, 2010;Ghoreschi et al, 2011;LaBranche et al, 2012). JAK inhibition by tofacitinib blocks signaling through the common g chain-containing receptors for several cytokines, including interleukin (IL)-2, -4, -7, -9, -15, and -21, and through receptors for cytokines such as IL-6, interferon-g (IFN-g), and type 1 IFN (Meyer et al, 2010;Ghoreschi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Maeshima et al (16) suggested that the therapeutic effect of tofacitinib results from inhibition of IFN-g and IL-17A. LaBranche et al (17) reported that tofacitinib suppressed arthritic joint structural damage by decreasing RANKL production.…”
Section: Discussionmentioning
confidence: 99%
“…Tofacitinib (CP-690,550), a pan-JAK inhibitor that is currently in use for the treatment of RA, was shown to suppress the production of IL-17 and IFN-g, as well as the proliferation of CD4 + T cells, under conditions of anti-CD3 and anti-CD28 stimulation (16), and to decrease T lymphocyte receptor activator for NF-kB ligand (RANKL) production (17). However, pan-JAK inhibitors may have safety issues linked to "off-target" effects, because JAK proteins are essential in signaling pathways that maintain physiological immune responses and processes, including hematopoiesis (18).…”
mentioning
confidence: 99%
“…The last chosen kinase inhibitor is tofacitinib (TOF; Figure 1c), which is a representative of the Janus kinase inhibitors (JAKIs). TOF is reported to selectively block the signaling pathway involving the kinases JAK 1 and 3 [8]. TOF was approved by the U.S. FDA in 2012 for the management of patients with moderate to severe rheumatoid arthritis (RA) either alone or to be taken with methotrexate in more sever un-responsive cases [9].…”
Section: Introductionmentioning
confidence: 99%